Undaria pinnatifida (U. pinnatifida) bioactivity: Antioxidant, gastro-intestinal motility, cholesterol biosynthesis and liver cell lines proteome. (August 2021) - Pedro, Bernardo; Guedes, Laura; André, Rebeca; Gaspar, Helena; Vaz, Pedro; Ascensão, Lia; Melo, Ricardo; Luísa Serralheiro, Maria
Graphical abstract: Highlights: Undaria pinnatifida prepared like a soup has phlorotannins and small peptides. Bioactive molecules in U. pinnatifida can inhibit acetylcholinesterase. Aqueous extract inhibits the activity of HMGR, reducing cholesterol biosynthesis. Several changes are induced in cell proteome with the U. pinnatifida aqueous extract. Abstract: Undaria pinnatifida is a brown alga, largely used as food in oriental countries. The purpose of this work was to analyze several bioactivities that might be present in different food preparations, relating them with the compounds present in the extracts. Aqueous extracts cooked, like a soup, as well as used in a salad, by simulating U. pinnatifida digestion with pancreatin were prepared. The soup preparation had anti-acetylcholinesterase activity as well as 3-hydroxy3-methyl-glutaryl coenzyme A reductase inhibition capacity, the use of 1 mg/mL, for both enzymes, caused 50% enzyme activity inhibition. The extracts produced changes in HepG2 cell proteome, mainly in the 148 kDa proteins. U. pinnatifida in salads hardly released phlorotannins to the digestive tract. The in vitro studies suggested that a soup prepared from this seaweed could deliver bioactive compounds, phlorotannins and small peptides that may facilitate the gastro-intestinal motility and reduce the cholesterol biosynthesis.